Effect of electron irradiation on the photovoltaic characteristics of GaAs p-n junctions - Dzhafarov, TD; Akciz, CS; Oren, D (ELSEVIER SCIENCE SA, 1998)
The influence of electron irradiation (Phi = 5 x 10(15)-1 x 10(17) cm(-2)) on photovoltaic characteristics of epitaxial and diffusion GaAs p-n junctions is investigated depending on the directions of electron beam and diffusion flux of acceptor impurity. For conditions of coincidence of these directions, degradation of photovoltaic parameters J(SC) (short-circuit photocurrent density) and V-OC (open-circuit voltage) of p-n junctions is larger than degradation of these parameters for opposite directions. The observed results are discussed on the basis of the model of drag of atoms lions) by fast electrons (i.e., due to origin of the 'electron wind'), that is caused by direct impact and transfer of part of the electrons' impulse to the impurity atoms. This, in turn stimulates the redistribution of concentrations of impurity in the p-n junction region and therefore, changes parameters of GaAs photocells. (C) 1998 Elsevier Science S.A.
Keywords: gallium arsenide; diffusion; liquid phase epitaxy; photo voltage; Materials Science; Physics